Structural Properties of Anode Composites Precursor of A Solid Oxide Fuel Cell Prepared Via Combustion Synthesis Route - Kalra, Pankaj; Garg, Rajeev; Grover, Neel Kanth; Kumar, Ajay (Asian Journal of Engineering and Applied Technology, 2012)
Solution combustion technique was used for the preparation of NiO-CGO (Ceria Gadolinia Oxide) composites – a precursor to SOFC anode by mixing cerium nitrate, gadolinium nitrate and nickel nitrate in stoichiometric ratio to form a precursor of composition Ce0.90Gd0.10O1.95 – 0.40 NiO. The concentration of oxidant i.e. glycine, was varied between 0.5 to 1.6 mole% and its effect was studied on the crystallite size and agglomerate of resulting NiO-CGO composite. The products formed were characterized by X-Ray Diffraction, Scanning Electron Microscope and Particle Size Analyzer. The results showed that the composite precursor varied in combustion characteristics, crystallite size and agglomerated particle size depending on the concentration of the fuel.